Fatores influenciadores na escolha pela medicina de família segundo estudantes numa região neotropical do Brasil - Afonso Henrique Teixeira Magalhaes Issa; Marco Tulio Antonio Garcia-Zapata; André de Castro Rocha; Bruna Baoini Sandré; Ana Caroline Ferreira Dutra; Isabella Luanna de Oliveira Martins; Marcos Wesley da Silva; Fátima Maria Lindoso da Silva Lima (UniEVANGÉLICA, 2018)
Objective: To analyze the perceptions of students in a medical school in the interior of a state of Goiás, on the factors influencing the choice or rejection of students by Family and Community Medicine as a medical career. Methodology: Qualitative, exploratory and transversal research. Content Analysis was adopted by Laurence Bardin. The instrument adopted was a script for a semi-structured interview and a socioeconomic questionnaire. The script had closed questions about which medical specialty the students were choosing. From then on, was asked why they chose or did not choose the Family and Community Medicine. Roadmap applied in 2013 to all 42 seniors in a medical school. Results: No students studied chose Family and Community Medicine. The social relevance of the specialty, the coverage of several different problems in clinical practice, the continuous link with patients and a greater exposure to this specialty, and especially the presence of experts in the undergraduate would be positive influences for the choice Family and Community Medicine. The lack of prestige in the university, identified in the discourse of preceptor teachers and doctors, in addition to the lack of recognition of society and the low remuneration were the main demotivating factors in this choice. Conclusion: The increase in the participation of more Family and Community Medicine specialists in the medical school, as well as a valuation in the university community and in the management of the health system can be actions that provoke a greater attraction of students to this specialty